The Marginal Cost of Public Funds: A Brief Guide - Spencer Bastani (Center for Economic Studies and ifo Institute (CESifo), 2023)
When deciding on the social desirability of public investment, the cost of a project is sometimes adjusted by a factor known as the Marginal Cost of Public Funds (MCPF) which captures the cost of raising public funds through distortionary taxation. However, there is no scholarly consensus on either its definition or its quantification. The purpose of this paper is to provide a brief up-to-date guide to the theoretical background, practical application, and empirical quantification of the MCPF, taking into account some recent developments in the public finance literature.
Keywords: D61; H41; H53; H21; 330; benefit-cost analysis; public investment; excess burden; distortions; public goods; taxes